2020
DOI: 10.1001/jamanetworkopen.2020.19169
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypothyroidism in Patients With Erdheim-Chester Disease

Abstract: Key Points Question What is the prevalence of hypothalamic-pituitary-thyroid dysfunction in patients with Erdheim-Chester disease (ECD)? Findings In this cross-sectional study of 61 patients with ECD, the prevalence of central and primary hypothyroidism was 9.8% and 18.0%, respectively, in patients with ECD, higher than the corresponding rates of 0.1% and 4.7%, respectively, in the community. Meaning The findings of this study su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…We did not find any sex, age or BMI differences in those with API. Furthermore, we found no association between inflammatory marker ESR and hsCRP, consistent with similar findings in hypothyroidism [9]. In contrast, previous findings suggested that increased systemic inflammation may accompany adrenal gland involvement [11].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We did not find any sex, age or BMI differences in those with API. Furthermore, we found no association between inflammatory marker ESR and hsCRP, consistent with similar findings in hypothyroidism [9]. In contrast, previous findings suggested that increased systemic inflammation may accompany adrenal gland involvement [11].…”
Section: Discussionsupporting
confidence: 89%
“…Panhypopituitarism and number of pituitary deficits (centrally occurring hypothyroidism, hypogonadism, DI, and adrenal insufficiency [AI]) were diagnosed by an endocrinologist based on the pituitary hormonal evaluation as outlined by the Endocrine Society guidelines [24]. Specifically, we performed serum free T4 and TSH to test for the hypothalamic-pituitary-thyroid axis, and any low normal or subnormal free T4 combined with low or inappropriately normal TSH was classified as central hypothyroidism [9,10,25]. Central hypogonadism was diagnosed on the basis of two morning serum total testosterone values below 300 ng/dL (or below our laboratory reference range) and low or inappropriately normal serum LH and FSH in association with hypogonadal symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ECD staging should exclude heart, central nervous system and endocrine system involvement with implications for treatment. Hypothyroidism is highly prevalent in ECD patients and may also constitute an adverse event of ECD treatment with interferon-alpha [ 15 , 16 ]. In our case, the primary involvement was the perirenal tissue infiltration with a risk for hydronephrosis and interferon-alpha was proposed as first line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…1,39,40 Hypothyroidism is another frequent endocrinopathy in AOH, and its manifestations (see Table 3) can potentially contribute to poor QoL. 41 Thyroid hormone replacement may help improve QoL and ameliorate symptoms. Providers should be aware that dosage adjustments to maintain a euthyroid state may be necessary during the course of the illness.…”
Section: Endocrine Issuesmentioning
confidence: 99%